The use of an omental flap for the reconstruction of a burn injury to the scalp: A case report - AlLababidi, Noor H. (Int J Surg Case Rep, 2018)
INTRODUCTION: Omental free flaps are used in reconstructing a wide range of clinical indications in the head and neck. The first omental flap case to be reported was in 1972 by McLean and Buncke. CASE PRESENTATION: This case demonstrate the feasibility of minimal invasive procedure of harvest an omental flap laparoscopically to cover the entire scalp after a burn injury in a young male. It is first to be reported in Saudi Arabia at our institute, Riyadh, 2012. A 14-year-old male had an extensive flame burn at the age of 2 years in the head and neck area. He received multiple skin grafting procedures and an amputation of the right hand, due to his chronic condition of recurrent open wounds the patient was admitted for removal of the unstable ulcer sting and scarred skin of the scalp and for coverage with omental free flap and split thickness skin graft. DISCUSSION: The coverage of wounds in the head and neck is usually done by using a local skin flap. The disadvantage of using the traditional skin flaps is difficulty to shape it in irregular, and large wounds. CONCLUSION: Owing its large size in covering wide defect, easy to shape in irregular edges over the bony surfaces, and high vascularity. This case demonstrate the feasibility of minimal invasive procedure of harvest an omental flap laparoscopically. We think that the use of omental flap is a useful flap and should be considered in the scalp and head and neck reconstruction.